TouchMover 2.0 – 3D Touchscreen with Force Feedback and Haptic Texture - Sinclair, Mike; Pahud, Michel; Benko, Hrvoje (Haptics Symposium 2014 (HAPTICS ’14), 2014)
This paper presents the design and development of a novel visiohaptic device that co-locates 3D stereo visualization, direct touch, texture and touch force sensing with a robotically actuated display. Our actuated immersive 3D display, called TouchMover 2.0, is capable of providing 1D movement (up to 36cm), haptic screen force feedback (up to 230N) in a single dimension perpendicular to the screen plane, and has an additional capability to render haptic texture cues via vibrotactile actuators attached to the touchscreen. We describe the details of our design and improvements. We showcase how TouchMover 2.0 allows the user to: touch and feel the 3D contour and 2D texture of a topographic map, to interact with 3D objects by pushing them on the screen with realistic force feedback and intuitively explore and feel pseudo tissue texture within volumetric data from medical imagery (e.g., MRI brain scan).